Analisis Peningkatan Citra Positif dari Habib Ja’far di Sosial Media dalam Perspektif Komunikasi Islam - Kusuma, Adhi; Arum, Aulia Senja; Afwan, Muhammad Kholis; Atahilah, Muhamad Ibnu; Wicaksono, Muhamad Rizqa; Nafisah, Siti Ibnu; Anshary, Ikmal; Ahmad, Pandi Rizqa (Peneliti.net, 2024)
A person's positive brand image is a legacy that has a significant impact on his career. A good image is important not only for attracting customers (in this example, mad'u), but also for revising material and mad'u satisfaction. Each da'i has its own specific way of transmitting Islamic teachings. Habib Ja’far uses social media, specifically Instagram, to spread his da'wah through photographs, films, colors, and infographics. This is a blend of artistic forms and conservative substance. Felix was able to capture the interest of young people by addressing this issue. Communicants who use Instagram no longer need to rely on the traditional manner of obtaining data or Islamic da'wah from specific preachers . Instagram provides the possibility to obtain statistics for followers. This study employs a qualitative descriptive approach with the goal of summarizing and describing various situations, conditions, or phenomena of social reality that exist and are interwoven in society and will be the subject of research, with the goal of bringing that reality to the surface as a characteristic, character, personality, characteristic, model, or reflection of the atmosphere, circumstances, or a specific phenomenon. Habib Ja’far, who is cognizant of the rapid development of this era, chose Instagram as a platform for preaching. Habib Ja’far usage of Instagram as a da'wah media is regarded as successful in terms of projecting a positive image to the public. Habib Ja’far methods of communication for preaching on Instagram include employing captions for each piece, preaching through novels, attractive images, and videos accompanied by preaching, and using animation as an attraction to transmit the word of da'wah. Habib Ja’far employs these four modes of communication to reach out to the Islamic communication process, ensuring that informed preaching messages are accepted and understood by the public